Changes in geomagnetic activity and global temperature during the past 40 years - Bucha, Václav, 1928- (Studia Geophysica et Geodaetica)
The purpose of this study is to investigate the effect of geomagnetic activity (used as a measure of solar wind parameters) on the variability of large-scale climate patterns and on changes in the global temperature. We show that positive statistically significant correlations between global temperature and the distribution of surface temperature over Eurasia, the East and Equatorial Pacific and over the North Atlantic for the period 1966–2009 correspond to large-scale climate patterns defined by climate indices. We found very similar positive correlations between geomagnetic activity and the distribution of surface temperature in the mentioned regions. As an effect of geomagnetic storms, energetic particles penetrate from the magnetosphere into the region of the stratospheric polar vortex. The increase of temperature and pressure can be observed over northern Canada. The vortex shifts towards Europe, rotates counter-clockwise and the wind blows from the polar region over Greenland southwards. It diverts the warm flow proceeding northward over the Atlantic, eastward along the deep Icelandic low extending as far as the Barents Sea and takes part in warming Eurasia. The strengthened zonal flow from Siberia cools the western Pacific with the impact on the warming of the equatorial and eastern Pacific when also a distinct 1976–78 climate shift occurred. Processes in the Atlantic and Pacific play a significant role and a time delay (wind forcing over the previous 1–4 yr) appears to be the most important for the relocation of the oceanic gyres. Results showing statistically significant relations between time series for geomagnetic activity, for the sum of climate indices and for the global temperature help to verify findings concerning the chain of processes from the magnetosphere to the troposphere. Václav Bucha. Obsahuje seznam literatury